Recent advancements toward therapeutic vaccines against Alzheimer's disease - Krystal Herline; Eleanor Drummond; Thomas Wisniewski (Taylor & Francis Group, 2018)
Introduction: Alzheimer's disease (AD) is a devastating neurodegenerative disease characterized by protein aggregates of amyloid β (Aβ) and tau. These proteins have normal physiological functions, but in AD, they undergo a conformational change and aggregate as toxic oligomeric and fibrillar species with a high β-sheet content. Areas covered: Active and passive immunotherapeutic approaches are among the most attractive methods for targeting misfolded Aβ and tau. Promising preclinical testing of various immunotherapeutic approaches has yet to translate to cognitive benefits in human clinical trials. Knowledge gained from these past failures has led to the development of second-generation Aβ-active immunotherapies, anti-Aβ monoclonal antibodies targeting a wide array of Aβ conformations, and to a number of immunotherapies targeting pathological tau. This review covers the more recent advances in vaccine development for AD from 2016 to present. Expert commentary: Due to the complex pathophysiology of AD, greatest clinical efficacy will most likely be achieved by concurrently targeting the most toxic forms of both Aβ and tau.